2016
DOI: 10.1002/chem.201604103
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Structurally Varied 1,3‐Disiloxanediols and Their Activity as Anion‐Binding Catalysts

Abstract: A series of new 1,3-disiloxanediols has been synthesized, including naphthyl-substituted and unsymmetrical siloxanes, and demonstrated as a new class of anion-binding catalysts. In the absence of anions, diffusion-ordered spectroscopy (DOSY) displays self-association of 1,3-disiloxanediols through hydrogen-bonding interactions. Binding constants determined for 1,3-disiloxanediol catalysts indicate strong hydrogen-bonding and anion-binding abilities with unsymmetrical siloxanes displaying different hydrogen-bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…Most likely, a fast conformational equilibrium as well as intramolecular dynamics associated with the hydrogen bridge in a cis conformer are responsible for proton exchange. However, intermolecular hydrogen bonding of 3 d is rather unlikely, since the self‐association of the comparable tetraphenyl‐1,3‐disiloxanediol was only observed at high concentrations or in the solid state . The 17 O{ 1 H} NMR spectrum of 3 d in C 6 D 6 changes negligibly when compared to the spectra in [D 8 ]THF.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Most likely, a fast conformational equilibrium as well as intramolecular dynamics associated with the hydrogen bridge in a cis conformer are responsible for proton exchange. However, intermolecular hydrogen bonding of 3 d is rather unlikely, since the self‐association of the comparable tetraphenyl‐1,3‐disiloxanediol was only observed at high concentrations or in the solid state . The 17 O{ 1 H} NMR spectrum of 3 d in C 6 D 6 changes negligibly when compared to the spectra in [D 8 ]THF.…”
Section: Resultsmentioning
confidence: 98%
“…Organosilanols show interesting properties, as their ability for hydrogen bonding can be associated, for example, with condensation reactions and applications in catalysis or drug design . Recently, Franz and co‐workers reported the hydrogen bonding driven self‐association and anion binding of various 1,3‐disiloxanediols . Organosilanols and siloxanediols in particular, can be regarded as models for surface‐bound silanol groups, which are abundant structural motifs in silicates and silica materials.…”
Section: Introductionmentioning
confidence: 99%
“…Given our previous work with disiloxanediols as H‐bond donor and anion‐binding catalysts, we evaluated the catalytic activity of POSS triol 1 a for the addition of indole ( 8 a ) to trans ‐β‐nitrostyrene ( 7 a ) (Table , Column 3). Despite enhanced H‐bonding activity based on TEPO data, POSS 1 a was found to yield comparable to silanediol 5 in o ‐DCB.…”
Section: Resultsmentioning
confidence: 99%
“…Our group and others have demonstrated that activity of organic, silanol‐containing hydrogen‐bond donor (HBD) catalysts can be tuned by silanol arrangement and acidity (e.g. 4 – 6 , Figure ) . Silanols display higher acidities compared with alcohols, which is attributed to hyperconjugation effects between the oxygen and silicon .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation